2005
DOI: 10.1103/physrevd.71.093008
|View full text |Cite
|
Sign up to set email alerts
|

Split supersymmetry at the logarithmic test of future colliders

Abstract: We consider a large number of pair production processes at future colliders (LHC, ILC) for values of the c.m. energy in the TeV range, where a logarithmic expansion of Sudakov kind would provide a reliable description of Split supersymmetric electroweak effects. We calculate all the leading and next to leading terms of the expansions, that would differ drastically in the considered domain from those of an extreme "light" scenario. We imagine then two possible competitive future situations, at LHC and at ILC, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…where √ S is the pp energy, L i j is the luminosity from partons i, j and the various kinematical variables are explained in details in [5].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where √ S is the pp energy, L i j is the luminosity from partons i, j and the various kinematical variables are explained in details in [5].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…They have quite different features as discussed in details in [4]. Application of the Sudakov technique to the three processes have been discussed in [5]. Here we discuss in some details the associated Wt production bg → tW − as a complete application of the previous general discussion.…”
Section: Single Top Production At Lhc: Sudakov Correctionsmentioning
confidence: 99%
“…It has been shown that the collinearb component of the inclusive process gg → tbW − can be attached as a QCD NLO correction to bottom quark distribution function of the exclusive process bg → tW − at the partonic level [7,8,9]. The LO contributions to tW − associated production is best considered to arise from the process bg → tW − .…”
Section: The Relevant Formulasmentioning
confidence: 99%
“…Its cross section is negligible at the T evatron but of considerable size at the LHC, where it is larger than that of the s-channel process for single top quark production. There is an extensive work on tW associated production at the LHC in the literature [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation